The indium-bearing minerals of the Pingüino polymetallic vein system, Deseado Massif, Patagonia, Argentina - Jovic, Sebastian Miguel (2011)
The Pingüino vein system forms part of the low-sulfidation epithermal mineralization associated with the Deseado Massif, Patagonia, Argentina. The ores are complex, with high tenors of Zn, Pb, Ag, Cd, Au, As, Cu, Sn, W and Bi. The mineralization developed in three stages: 1) an early Cu–As–Sn-(W–Bi–Ag–Au–In) stage (Ps1), 2) a Zn–Pb-(Ag–In–Cd–Sb) stage (Ps2), and 3) a late Zn–Cd–In stage (Ps3). The polymetallic veins show a wide range of indium concentration (3.4 to 1184 ppm In). The highest values were achieved during the Ps2 stage of mineralization, although significant In anomalies are also present in Ps1 (up to 159 ppm). Three types of In association can be distinguished, on the basis of a microanalytical study of the ores. Iron-rich sphalerite from Ps2, volumetrically important at this stage, has very high In contents (up to 2.56 wt.% In), and therefore is the most important carrier of In at Pingüino. Tin minerals (ferrokësterite and cassiterite) in the Ps1 assemblage are the second carriers in importance in these deposits, and their In contents may attain up to 3.02 wt.%. The third type is represented by greenockite crystals from assemblage Ps3, which presents important In contents (up to 3.63 wt.%), but these minerals are scarce in the deposit. The presence of high values of In and of Zn, Pb, Ag, Au, Cu, Sn, W and Bi in the polymetallic veins of the Pingüino vein system opens interesting possibilities for mineral exploration in the Deseado Massif.